Broadening the Spectrum of Adulthood X-Linked Adrenoleukodystrophy: A Report of Two Atypical Cases - Foschi, Matteo; Vacchiano, Veria; Avoni, Patrizia; Incensi, Alex; Battaglia, Stella; Donadio, Vincenzo; Panzeri, Elena; Bassi, Maria Teresa; Liguori, Rocco; Rizzo, Giovanni (Frontiers in Neurology, 2019)
X-linked adrenoleukodystrophy (x-ALD) is a rare genetic disorder caused by a mutation in the ABCD1 gene, which encodes for a peroxisomal very long chain fatty acid transporter. Clinically, x-ALD can present a wide spectrum of different phenotypes: asymptomatic carriers, Addison only, cerebral x-ALD, and myelopathy with/without evidence of peripheral axonopathy (Adrenomyeloneuropathy). We report on two cases of adult x-ALD, with atypical phenotypes: (Case 1) A 37-years-old male with a 2-years-long history of spastic paraparesis, urinary urgency, and subclinical adrenocortical insufficiency. As an atypical finding, the MRI showed multiple congenital brain development defects. (Case 2) A 63-years-old male with a previous diagnosis of Addison disease, with a 6-years-long history of spastic paraparesis. Two years later, he complained of severe and disabling burning pain in his feet. A nerve conduction study was normal, but a skin biopsy revealed autonomic and somatic small fiber neuropathy. In both cases, genetic testing disclosed hemizygous mutation in ABCD1 associated with x-ALD: c.1394-2A > G and p.(Thr254Met), respectively. While case 1 supports the key role of peroxisome functions in brain development, case 2 points to a possible selective and clinically relevant peripheral small fiber degeneration in x-ALD myelopathy.